Model Pembelajaran Pendidikan Agama Islam Berbasis Quantum Teaching di SMP Muhammadiyah 2 Medan - Alhafiz, Jehandra; Anisa, Pina; Badri Girsang, Hamidah Nurul (Yayasan Rahmat Islamiyah, 2024)
Religious education is a structured effort to teach religious values, in this case the effort includes cognitive, emotional and psychomotor aspects, but failed. This failure is caused by the failure of education to produce human resources who are critical, creative, innovative, dignified, ethical and moral. So far the new learning process has been able to touch cognitive and emotional aspects so that it makes a significant contribution in reaching the psychomotor domain. The latter is very important for religious communities. This is related to human sensitivity in social life. Seeing this reality, serious attention needs to be given to Islamic education, especially in Indonesia, to demand empowerment and contribute to efforts to reshape this situation. Of course, this need takes into account the connectedness and role of the Indonesian community, which is predominantly Muslim, in educational activities. Therefore, considering changing times, breakthroughs are needed such as changes to models and implementation strategies.